Types of vessels adopted in the Algerian Navy between the sixteenth and nineteenth centuries - ouhamchouche, naima (The Algerian Historical Journal, 2026)
After joining the Ottoman Caliphate in 1519, Algeria sought make military efforts in cooperation with the Ottomans and before the increase of European harassment and naval attacks against it, it took care of the development of its navy. Because of its strategic loction in front of Europe, Algeria has become an advanced base for the Islamic world, making it necessary to take care of its fortifications and its fleet. As long as the competitiveness of the ship guaranteed maritime sovereignty and secure borders, Algerians focused on the construction and armament of vessels, making the Algerian ship unique with special characteristics